William : HRH Prince William of Wales - Graham, Tim; Archer, Peter (London Simon & Schuster, 2003)
A pictorial celebration of the 21st birthday of Prince William that will appeal to admirers, collectors and Royal watchers everywhere. Many of the photographs have never been published before and are accompanied by a text written by a journalist accredited to both Buckingham Palace and St James's.
Include Illustrations.
HRH Prince William of Wales.
Keywords: Princes -- Great Britain -- William, Prince, Duke of Cambridge, 1982-